THE INFLUENCE OF HIJAB FASHION TRENDS ON CONSUMPTIVE BEHAVIOR OF ISLAMIC BANKING STUDENTS AT IAIN PEKALONGAN - Fikri Amalia Rosyada; Hendri Hermawan Adinugraha (Journal of Management and Islamic Finance, 2022)
Fashion is an important thing in the lives of teenagers and adults. Fashion is considered to provide a reflection of each person. The development of the hijab fashion trend is also developing among Muslims, especially among female students. The desire to follow the hijab fashion trend causes extravagant behaviour to support appearance. The purpose of this study is to analyze the effect of hijab fashion trends on the consumptive behaviour of Islamic Banking students at IAIN Pekalongan. The method used in this study was a qualitative method using a phenomenological approach and data collection using the methods of observation, interviews, and documentation. Meanwhile, the research subject was Islamic Banking student taken by purposive sampling method. The results of this study indicate that the hijab fashion trend has a significant influence on the consumptive behaviour of Islamic Banking students. The consumptive behaviour of female students is shown by the hijab worn on campus with various styles that are trends and a waste of buying hijab with the desire to fulfil their fashion style so that they can look attractive when leaving for campus.